The real-world economic impact of home-based video electroencephalography: the payer perspective. (3rd October 2019) - Slater, Jeremy D.; Eaddy, Michael; Butts, Conor M.; Meltser, Inna; Murty, Sharanya
Abstract: Aims: Electroencephalography (EEG) is an established method to evaluate and manage epilepsy; video EEG (VEEG) has significantly improved its diagnostic value. This study compared healthcare costs and diagnostic-related outcomes associated with outpatient vs inpatient VEEG among patients with epilepsy in the US. Materials and methods: This study used Truven MarketScan Commercial and Medicare Supplemental claims databases. Patients with a VEEG between July 1, 2013 and December 31, 2016 were identified. Index event was the first VEEG claim, which was used to determine inpatient and outpatient cohorts. Continuous health plan enrollment 6 months pre- and 12 months post-index VEEG was required. Primary outcomes were costs during the index event and 12 months post index. A generalized linear model with gamma distribution and a log link was used to estimate adjusted index and post-index costs. Results: Controlling for baseline differences, epilepsy-related cost of index VEEG was significantly lower for the outpatient (4, 098) vs the inpatient cohort (13, 821; p < 0.0001). The cost differences observed at index were maintained in the post-index period. The 12-month post-index epilepsy-related costs were lower in the outpatient cohort (6, 114 vs 12, 733, p < 0.0001). Time from physician referral to index VEEG was significantly shorter in the outpatient cohort (30.6 vs 42.5 days). Patients in the inpatient cohort were also more likely to undergo an additional subsequent follow-up inpatient VEEG ( p < 0.0001). Limitations: Administrative claims data have limitations, including lack of data on clinical presentation, disease severity, and comprehensive health plan information. Generalizability may be limited to a US insured population of patients who met study criteria. Conclusions: Index VEEG was less costly in an outpatient vs inpatient cohort, and costs were lower during the follow-up period of 12 months, suggesting that outpatient VEEG can be provided to appropriate patients as a less costly option. There were fewer follow-up tests in the outpatient cohort with similar pre- and post-index diagnoses.